Contextual problem-based project-based learning as an effective strategy to improve science process skills and science achievement - Nyoman Maesha Bramanda; I Gusti Ngurah Pujawan; I Dewa Ayu Made Budhyani (Jurnal Inovasi dan Teknologi Pembelajaran, 2026)
This study examines the effect of a contextual problem-based Project Based Learning (PjBL) model assisted by E-LKPD on science process skills and science learning achievement of fifth-grade elementary school students. This research employed a quasi-experimental method with a posttest-only control group design involving two intact classes in the Diponegoro Cluster, West Denpasar. Data were collected using a science achievement test and an observation sheet of science process skills and analyzed using MANOVA. The results indicate that students taught through contextual problem-based PjBL assisted by E-LKPD achieved significantly higher science process skills and science learning achievement than those taught using conventional instruction, both partially and simultaneously. Practically, this learning model supports the implementation of the current competency-based curriculum by promoting student-centered learning, strengthening scientific inquiry skills, and facilitating meaningful science learning through contextual project activities in elementary schools.